2009
DOI: 10.1176/appi.ajp.2009.08040613
|View full text |Cite
|
Sign up to set email alerts
|

Randomized, Double-Blind, Placebo-Controlled Study of Paliperidone Extended-Release and Quetiapine in Inpatients With Recently Exacerbated Schizophrenia

Abstract: Compared with quetiapine, paliperidone extended-release improved symptoms earlier and to a greater degree in patients with recently exacerbated schizophrenia requiring hospitalization, with no unexpected tolerability findings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
38
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(39 citation statements)
references
References 29 publications
1
38
0
Order By: Relevance
“…The current population and flexibledose design were chosen to reflect a more representative patient sample treated in a naturalistic setting with treatment that closely resembles day-to-day clinical practice. These data help support results from previously published, fixed-dose, randomized clinical trials [11][12][13][14] . It is important to recognize that concomitant medications, particularly benzodiazepines, and hospitalization may have contributed to some of the benefits, including early response, seen with paliperidone ER.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…The current population and flexibledose design were chosen to reflect a more representative patient sample treated in a naturalistic setting with treatment that closely resembles day-to-day clinical practice. These data help support results from previously published, fixed-dose, randomized clinical trials [11][12][13][14] . It is important to recognize that concomitant medications, particularly benzodiazepines, and hospitalization may have contributed to some of the benefits, including early response, seen with paliperidone ER.…”
Section: Discussionsupporting
confidence: 87%
“…Benzodiazepines were used by 75-78% of patients in one study 11 ; rescue medications were used by 54-72% of patients in the other two studies, with benzodiazepines reported to be the most commonly used rescue therapies 12,13 . A subsequent 6-week, double-blind, randomized, controlled study with paliperidone ER, quetiapine, or placebo arms was less restrictive by permitting additional psychotropic medication after 2 weeks of initial assigned therapy, with 53% of patients being treated with supplemental therapy, most commonly antipsychotics 14 . Finally, although randomized trials evaluated efficacy starting 4 days after treatment initiation, information on earlier clinical response is important in clinical practice when managing acute schizophrenia, particularly among hospitalized patients as were used in the clinical trials.…”
Section: Introductionmentioning
confidence: 99%
“…The ziprasidone studies [37][38][39] indicated that somnolence rates were positively correlated to study durations. However, the paliperidone studies did not show a similar correlation between somnolence rates and paliperidone treatment duration [29][30][31][32]. Two maintenance studies [40,41] showed no significant differences in somnolence rates between antipsychotics and placebo ( Table 1).…”
Section: Acute and Maintenance Active Treatment Versus Placebomentioning
confidence: 95%
“…Does evidence exist that any medication will reduce hostility in patients With schizophrenia spectrum disorders? 34,48,49,51,52,54,55,[103][104][105][106][107][108][109][110][111][112][113] ( Table 2) Eighteen articles were identified that reported relevant data. No Class I studies were identified that tested this hypothesis.…”
Section: Resultsmentioning
confidence: 99%